2020
DOI: 10.1136/annrheumdis-2020-218013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 pandemic on patients with SLE: results of a large multicentric survey from India

Abstract: Table 1 Demographics and clinical characteristics of patients with SLE with confirmed or suspected COVID-19 COVID-19-like clinical picture (group A)* Contact with patient with COVID-19 (group B)*

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…During the COVID‐19 pandemic, studies in Asia showed that only 0.1%‐0.2% of SLE patients had documented infection with COVID‐19 85‐89 (Table 5). Together with other case series and reports, there is a total of 18 reported SLE patients with COVID‐19 infection 90‐94 .…”
Section: Resultsmentioning
confidence: 99%
“…During the COVID‐19 pandemic, studies in Asia showed that only 0.1%‐0.2% of SLE patients had documented infection with COVID‐19 85‐89 (Table 5). Together with other case series and reports, there is a total of 18 reported SLE patients with COVID‐19 infection 90‐94 .…”
Section: Resultsmentioning
confidence: 99%
“…All of our patients had RA. On the other hand, a previous Indian report cited one case of COVID-19 among 845 patients with lupus [12]. However, among this cohort 17 had suspect symptoms, among which only two were tested.…”
Section: Discussionmentioning
confidence: 86%
“…8 Another multicentric survey from our country included 845 patients of SLE and reported only two cases of COVID-19. 18 The COVID-19 Global Rheumatology Alliance had reported 600 cases of COVID-19 in patients with underlying rheumatological disorders. Of these 600 patients, 85 (14%) had underlying SLE.…”
Section: Discussionmentioning
confidence: 99%